The Effect of Giving Paklobutrasol and Calcitor Fertilixer on The Yield of Siamese Citrus - I Komang Juniarta; Ni Putu Anom Sulistiawati; Ni Komang Alit Astiari (Warmadewa University Press, 2022)
The purpose of this study was to determine the effect of giving paklobutrasol and calcitor fertilizer and their interaction on the yield of Siamese orange (Citrus nobillis var microcarva L.) conducted in Bayung Gede Village, Kintamani District, Bangli Regency from December 2021 to July 2022. This study using a randomized block design (RAK) with 2 factors arranged in a factorial manner. The first factor that was tried was the administration of Paklobutrazole (P) which consisted of 4 levels, namely: P0 (0 cc/L water), P1 (5 cc/L water), P2 (10 cc/L water). P3 (15 cc/L water) while the second factor is the application of calcitor fertilizer (K) which consists of 4 levels, namely: K0 (0 cc/L water), K1 (3 cc/L water), K2 (6 cc/L water ), K3 (9 cc/L water). Thus, there were 16 combination treatments, each of which was repeated 3 times so that 48 citrus trees were needed. The results showed that the interaction between the administration of Paklobutrasol and Kalsitor Fertilizer (PxK) had no significant effect on all observed variables. The highest harvested fruit weight per tree was obtained in the treatment with Paklobutrasol 15cc/tree, which was 7.77 kg or an increase of 78.21% when compared to the treatment without Paklobutrasol, which was 4.36 kg, while the highest harvested fruit weight per tree was obtained in the treatment with Calcitor Fertilizer 9cc/tree, which was 6.90. kg or an increase of 28.49% compared to the treatment without the application of calcitor fertilizer, namely 5.37 kg.